Formation of silver NANOSTRUCTURES by immersion deposition method onto POROUS SILICON and study of their optical properties - K. V. Girel; H. V. Bandarenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Nanostructures formed by immersion deposition of silver on porous silicon at different regimes for their application in surface enhanced Raman spectroscopy (SERS) has been presented. Porous silicon has been fabricated by anodization of monocrystalline silicon in water solution of isopropanol and hydrofluoric acid. Reflectance spectra of the obtained structures of silver/porous silicon have been studied. It has been revealed that the optimal regimes of SERS require using laser with wave length of 400-450 nm.